2020
DOI: 10.1158/0008-5472.can-20-1011
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Spatial and Temporal Heterogeneity in Bevacizumab-Treated Breast Tumors by Eigenspectra Multispectral Optoacoustic Tomography

Abstract: Understanding temporal and spatial hemodynamic heterogeneity as a function of tumor growth or therapy affects the development of novel therapeutic strategies. In this study, we employed eigenspectra multispectral optoacoustic tomography (eMSOT) as a next-generation optoacoustic method to impart high accuracy in resolving tumor hemodynamics during bevacizumab therapy in two types of breast cancer xenografts (KPL-4 and MDA-MB-468). Patterns of tumor total hemoglobin concentration (THb) and oxygen saturation (sO2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 55 publications
2
20
1
Order By: Relevance
“…Liapis et al. ( 36 ) highlight the importance of data collection immediately following the administration of therapeutic agents. Similarly, Hysi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liapis et al. ( 36 ) highlight the importance of data collection immediately following the administration of therapeutic agents. Similarly, Hysi et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study did not choose to examine pretreatment conditions (i.e., volume or baseline StO 2 ). A recent study by Liapis et al (36) longitudinally examined tumor hemodynamics in two types of breast cancer xenografts focusing particularly on HbT and StO 2 changes with the administration of bevacizumab, a drug that targets circulating VEGF and prevents it from attaching to its cell membrane receptors. They observed a sharp drop in tumor StO 2 and HbT concentration shortly after initiation of treatment that was then restored back to pretreatment levels.…”
Section: Introductionmentioning
confidence: 99%
“…Some preclinical studies revealed tumor shrinkage after anti-VEGF therapy, others suggesting vascular normalization have been related to increased rates of tumor growth [108]. Data from clinical studies in breast cancer and glioblastoma patients treated with bevacizumab are also contradictory, with some studies reporting increased oxygenation in tumors, and others describing aggravation in intratumoral hypoxia [109]. Besides, the induction of hypoxia by anti-angiogenic agents have been proven to increase numbers of breast cancer stem cells [110].…”
Section: Vessel Normalizationmentioning
confidence: 99%
“…Thus, this approach might be exploited in the future to monitor the response of pseudohypoxic PCC cells to anti-angiogenic drugs in vivo. Recent studies have demonstrated the high quality of the vessel resolution by MSOT in breast cancer and its suitability to monitor drug treatment response [ 80 ], thereby suggesting that this modality might be applicable to preclinical PPGL research as well.…”
Section: Introductionmentioning
confidence: 99%